2020
DOI: 10.1016/j.jaci.2019.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of implementing objective diagnostic verification of asthma in the United States

Abstract: Background: Asthma diagnosis in the community is often made without objective testing. Objective: The aim of this study was to evaluate the cost-effectiveness of implementing a stepwise objective diagnostic verification algorithm among patients with community-diagnosed asthma in the United States. Methods: We developed a probabilistic time-in-state cohort model that compared a stepwise asthma verification algorithm on the basis of spirometry testing and a methacholine challenge test against the current standar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Aaron et al reported that nearly one-third of patients with physician-diagnosed asthma could not be verified when using objective testing such as peak flow, spirometry, and bronchoprovocation [7]. Several studies have demonstrated that the overall cost of misdiagnosing asthma can be substantial [2,[18][19]. While healthcare cost varies by systems and locations, one study noted that the average annual cost per person was $3,266 [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aaron et al reported that nearly one-third of patients with physician-diagnosed asthma could not be verified when using objective testing such as peak flow, spirometry, and bronchoprovocation [7]. Several studies have demonstrated that the overall cost of misdiagnosing asthma can be substantial [2,[18][19]. While healthcare cost varies by systems and locations, one study noted that the average annual cost per person was $3,266 [2].…”
Section: Discussionmentioning
confidence: 99%
“…Yaghoubi and colleagues extrapolated their findings to the US populations for a potential savings of over $56 billion over 20 years [19]. Even in smaller cohorts, such as the population of the JDACs, improper asthma diagnoses can add unnecessary burdens to the overall cost of incarceration and divert funding and resources from other essential services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct annual costs due to having asthma by the control levels and having exacerbation by the severity levels were extracted from Yaghoubi et al (2020). The costs were converted from 2018 USD to 2023 CAD using historical inflation (1 USD in 2018 = 1.22 USD in 2023; 1 USD = 1.36 CAD in 2023).…”
Section: Payoffs Modulementioning
confidence: 99%
“…Aldington and Beasley ( 2007), Yaghoubi et al (2020), Einarson et al (2015) Direct annual costs due to asthma control Let 𝑐 ) 3 be the direct annual costs due to asthma control level 𝑗. Then the total cost due to asthma control is given by: ∑ 𝑐 ) 3 ) 𝐶𝑇 ) .…”
Section: Einarson Et Al (2015)mentioning
confidence: 99%